Marketing strategies and export performance of fresh produce firms in Kenya - Anne Njonjo; Winnie Njeru; Francis N. Kibera; Joseph Owino (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
The study objective was to examine the role of marketing strategies on export performance of fresh produce firms in Kenya. A major stream of research has considered marketing strategy and performance within the context of a domestic economy. A census survey was carried out among all the 100 fresh produce firms that were ordinary members of the Fresh Produce Export Association of Kenya (FPEAK) as at 31 st June 2019. The study utilized a positivist approach. Primary data were collected using a structured questionnaire. A descriptive cross-sectional study design was adopted. The results of regression analysis revealed that the relationship between marketing strategies and export performance was positive and statistically significant. To policy makers, the study recommends regional and bilateral trade agreements that seek to increase the market share for fresh produce firms. To management practice, the study provides guidelines on how to design and implement sustainable but competitive marketing strategies for the export market. For future research direction, the study recommends additional moderating/mediating variables that may infl uence export performance.
Keywords: M30; M31; N57; N77; 650; marketing strategies; export performance; marketing mix; exports